DINAMIKA AIR DAN FASE-FASE PERKEMBANGAN PEMBUNGAAN PENENTU PRODUKTIVITAS KELAPA SAWIT - Iman Yani Harahap; Muhammad Edwin Syahputra Lubis (Pusat Penelitian Kelapa Sawit, 2018)
To identify flowering development phases that most determines oil palm yield in relation to water dynamics, a research had been conducted at Indonesian Oil Palm Research Institute (IOPRI) experimental garden in Tandun, Riau. The variables observed were water parameters including rainfall, groundwater level, soil water content, and the rate of increase in capillary water at 0 – 200 cm soil depth. Rrelationship between water parameters and oil palm yield was analyzed using correlation statistics and multiple linear regression models. Analysis of multiple linear models was performed using stepwise regression techniques to select the most powerful parameters determining the relationship between independent and non-independent variables. MATLAB R2017b software was used for data processing. The study showed that phases of flower bunch development at certain time prior physiological maturity determined monthly oil palm yield. Critical phases affected oil palm yield were formation of flower crown, sex differentiation, appearence of flower buds, and ripening of fruit bunches. Compared to other flower developmental phases, the phase of sex differentiation of flowers that occurred 20 months before the fruit bunches were physiologically mature was the most critical phase in determining monthly yield of oil palm.